2018
DOI: 10.1155/2018/5201786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tyrosinase Inhibitory, Antioxidant, Antimicrobial, and Antiaging Activities of Magnolia officinalis Extracts after Aspergillus niger Fermentation

Abstract: This study intended to improve physiological characteristics of Magnolia officinalis bark (MOB) extracts by Aspergillus niger fermentation. M. officinalis bark was extracted using distilled water, 95% ethanol, and methanol, and it was then fermented by A. niger. The physiological characteristics of the fermented extracts, namely, tyrosinase inhibitory activity, antioxidant activity, antibacterial activity, and anti-skin-aging activity, were evaluated and compared with those of unfermented extracts. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 47 publications
(64 reference statements)
1
39
0
Order By: Relevance
“…In particular, samples fermented with L. acidophilus had superior inhibitory activity . Similar findings were obtained for Magnolia officinalis extracts fermented with Aspergillus niger and the improvements in tyrosinase inhibitory activity and other physiological activities were attributed to the concentration of the inherent bioactive compounds in the sample as well as the biosynthesis of new compounds with significant biological activities …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, samples fermented with L. acidophilus had superior inhibitory activity . Similar findings were obtained for Magnolia officinalis extracts fermented with Aspergillus niger and the improvements in tyrosinase inhibitory activity and other physiological activities were attributed to the concentration of the inherent bioactive compounds in the sample as well as the biosynthesis of new compounds with significant biological activities …”
Section: Discussionsupporting
confidence: 76%
“…However, too much melanogenesis and accumulation on the upper layer of the skin may be unfavorable. Hence, the use of substances that can inhibit the activity of tyrosinase has become important as these inhibitors target the specific melanin‐producing cells and do not lead to undesirable effects as compared to other compounds that can prevent melanin production and accumulation . The fermented samples inhibited the activity of tyrosinase to a greater extent as compared to the unfermented sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Assay content and diffusion per hour release content was analyzed using the equation obtained by linear regression analysis from calibration curve of Kojic acid and Arbutin by HPLC method . In‐vitro Skin irritation study and tyrosinase activity study were performed to determine the cosmetic safety anti‐hyperpigmentive activity of the formulation …”
Section: Methodsmentioning
confidence: 99%
“…33. Additionally, none of the volunteers suffered skin irritation or allergic reactions during the test 258 period.…”
mentioning
confidence: 99%
“…In the past few decades, research has demonstrated that natural bioactive compounds are increasingly being used in whitening cosmetic formulations. In addition, there are several plant extracts that have been shown to be effective agents to suppress the overproduction of melanin or to regulate melanin synthesis, such as Cassia fistula flowers [31], Asphodelus microcarpus [32], Magnolia officinalis [33], Dendrobium tosaense [34], and Kummerowia striata [35]. The results of the present study indicated that extracts of E. elatior flowers and leaves achieved a decent skin whitening effect on human volunteers; therefore, these extracts act as the active whitening ingredient in FL1 cream.…”
mentioning
confidence: 99%